Classification of Poverty in Maluku Province using SMOTE-Random Forest Algorithm - Ferina L Damamain; Lexy Janzen Sinay; Sanlly J Latupeirissa; Lusye Bakarbessy (Pattimura International Journal of Mathematics (PIJMath), 2025)
Poverty is a complex issue. According to BPS publications, in 2023, the poverty line in Indonesia has reached 9.57%. Maluku is one of the provinces with a high poverty rate, reaching 16.23%. This research aims to classify poverty status in Maluku Province using the SMOTE-random forest algorithm. This research uses SUSENAS 2022 data, where the data is not balanced. SMOTE is used to overcome this problem. The best model obtained has an accuracy rate of 85.8%. The model is based on a training data proportion of 75% and testing 25%, with parameters m=4 and r=100. The critical factor that influences poverty status in Maluku Province is the number of households.